Pro F.I.T Market Efficiency Learning Toolkit - Jasni, Nur Syuhada; Mat Rahim, Nurhazrina; Adnan, Mohd Fairuz; Ahmad, Bedah (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Understanding the stock market can be complex, especially when learning about the Efficient Market Hypothesis (EMH). Many students struggle with financial concepts due to their abstract and theoretical nature. To address this, we developed Pro F.I.T. – Market Efficiency Learning Toolkit, an interactive and engaging approach to finance education. The F.I.T. strategy—Find, Invest, Time—simplifies how stock prices react to information. This toolkit incorporates quizzes, simulations, and real-world case studies to help students understand the three forms of EMH (Weak, Semi-Strong, and Strong). Through hands-on activities, learners can see how stock prices fluctuate based on news, corporate performance, and market events. This project enhances financial literacy by making learning practical and engaging. Instead of memorizing theories, students will apply concepts through interactive learning models. The toolkit is suitable for schools, investment clubs, and financial literacy programs, with potential expansion into a mobile app or university training program. By making financial concepts clear, engaging, and rewarding, the F.I.T. Market Efficiency Learning Toolkit helps students develop critical thinking, decision-making, and investment skills, fostering a deeper understanding of financial markets. This project aims to revolutionize finance education and stock market learning for young learners.